2008
DOI: 10.2308/jata.2008.30.2.21
|View full text |Cite
|
Sign up to set email alerts
|

Investor Response to a Reduction in the Dividend Tax Rate: Evidence from the Jobs and Growth Tax Relief Reconciliation Act of 2003

Abstract: This study examines investor reaction to the reduction in federal income tax rates on dividends resulting from passage of the Jobs and Growth Tax Relief Reconciliation Act of 2003 (JGTRRA or the Tax Act). We investigate the existence of a clientele shift associated with the JGTRRA by examining trading volume in dividend-paying stocks surrounding passage of the Tax Act. Also, we examine changes in shareholder composition of firms over the period between announcement in the press and final passage of the plan. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, several prominent studies applying event study method to analyse the market reaction of tax news found inconsistent results. Such as positive association between tax news and stock prices have been exhibited by Baltagi et al (2006), Edwards, Lang, Maydew, and Shackelford (2004), Howton and Howton (2006), Hu (1998), Lightner, Morrow, Ricketts, andRiley (2008), Umlauf (1993) whereas, Amromin, Harrison, and Sharpe (2008), Gallemore, Maydew, and Thornock (2014), Hanlon and Slemrod (2009), Hill, Kubick, Lockhart, and Wan (2013) found a negative association between tax news and the aggregate market value of the corporations. Moreover, no significant market reaction to tax news has been found by Amromin, Harrison, Liang, and Sharpe (2005).…”
Section: Research Question and Hypothesis Developmentmentioning
confidence: 79%
“…However, several prominent studies applying event study method to analyse the market reaction of tax news found inconsistent results. Such as positive association between tax news and stock prices have been exhibited by Baltagi et al (2006), Edwards, Lang, Maydew, and Shackelford (2004), Howton and Howton (2006), Hu (1998), Lightner, Morrow, Ricketts, andRiley (2008), Umlauf (1993) whereas, Amromin, Harrison, and Sharpe (2008), Gallemore, Maydew, and Thornock (2014), Hanlon and Slemrod (2009), Hill, Kubick, Lockhart, and Wan (2013) found a negative association between tax news and the aggregate market value of the corporations. Moreover, no significant market reaction to tax news has been found by Amromin, Harrison, Liang, and Sharpe (2005).…”
Section: Research Question and Hypothesis Developmentmentioning
confidence: 79%
“…Moser and Puckett (2009) and Jun et al (2011) find a dividend tax clientele effect on institutional investors. Lightner et al (2008) find support for a shareholder clientele effect in dividend-paying firms following the 2003 US tax reform. Ayers et al (2002) report a negative relationship between share values and an increase in the individual…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 81%
“…As a result, stock prices increased and the cost of equity capital declined. (i.e., Dhaliwal et al 2007; Auerbach and Hassett 2007;and Lightner et al 2008). Empirical tax research on JGTRRA so far has supported the idea that taxes on individual shareholders affect the pricing of stocks.…”
Section: Introductionmentioning
confidence: 95%